Among the efforts of contemporary Iraqi researchers and writers in the study and investigation of Abbasid poetry (Journal of the College of Basic Education, 2022)
Researchers and scholars, past and present, have been interested in Abbasid poetry, whose period extends from the year 132 AH to 656 AH.